Seed-induced Aβ deposits in the corpus callosum disrupt white matter integrity in a mouse model of Alzheimer’s disease - Aires, Vanessa; Ziegler-Waldkirch, Stephanie; Friesen, Marina; Reichardt, Wilfried; Erny, Daniel; Loreth, Desiree; Harborne, Andrew; Kretz, Oliver; von Elverfeldt, Dominik; Meyer-Luehmann, Melanie (Frontiers in Cellular Neuroscience, 2022)
Neuropathologically, Alzheimer’s disease (AD) is characterized by the accumulation of Aβ and subsequent formation of the so-called Aβ plaques. Along with neuronal loss, previous studies report white matter anomalies and corpus callosum (CC) atrophy in AD patients. Notably, perturbations in the white matter can be observed years prior to expected disease onset, suggesting that early stages of disease progression play a role in AD-associated loss of myelin integrity. Via seed-induced deposition of Aβ, we are able to examine alterations of CNS integrity during the initial stages of plaque formation. In this study, we investigate the impact of Aβ seeding in the CC utilizing various imaging techniques as well as quantitative gene expression analysis and demonstrate that Aβ deposits result in an imbalance of glial cells in the CC. We found increased amounts of phagocytic microglia and reactive astrocytes, while oligodendrocyte progenitor cell numbers were reduced. Moreover, white matter aberrations adjacent to the Aβ seeding were observed together with an overall decline in callosal myelination. This data indicates that initial stages of plaque formation induce oligodendrocyte dysfunction, which might ultimately lead to myelin loss.